Peranan Keluarga Sakinah Mawaddah Wa Rahmah Dalam Mempererat Kesatuan Bangsa - Muhammad Sakir; Mursalim; Ahmad Syafi'i (Tasamuh: Jurnal Studi Islam, 2024)
Indonesia's failing educational output is an inescapable reality of life. The high failure rate is caused by inappropriate family education. This research aims to emphasize that the role of a sakinah, mawaddah, wa rahmah family through character education can strengthen national unity. Comprehensively, this paper examines; (1) What is the role of the family in character building? (2) Why can the existence of the family be said to be a pillar in society? and (3) What is the form of a family that is sakinah, mawaddah and wa rahmah? Through the library research method using a descriptive approach, this research shows that the family acts as an agent of national character building through fostering children at home, the family is also a pillar in society for the benefit of the people, and a good family is a family that is sakinah, mawaddah, wa rahmah.